Analysis of Community Empowerment Through a Waste Management Program in Medan Denai District, Medan City - Khaidir, Khaidir; Agus, Efendi; Syafruddin, Syafruddin (Universitas Medan Area, 2024)
The Medan Denai Locale Government has as of late been currently moving towards a spotless climate. Medan Denai Locale will be a model for other sub-regions in their endeavors to work on the nature of a perfect climate. The deterrent faced by individuals of Medan Denai Locale is an absence of inspiration and mindfulness regarding the significance of ecological tidiness. The arrangement that should be possible to conquer these obstructions is by holding a strengthening program completed by the Medan Region government for the local area with the exercises of the Drape Program, the Night Squander Apportioning Project (persami), the Denai Quick Waste Help (persad), and the Waste Development Program for Denai hindering (Denai guardians). The point of this program is to engage the local area by imparting local area mindfulness and worry as well as being straightforwardly associated with molding the climate through related programs. The strategy involved is to gather information through direct perception in the encompassing Medan Denai Locale region by focusing on the treatment of moved squander and keeping up with tidiness over the day. This community empowerment program has allowed Medan Denai District to improve, maintain, and even develop its environmental cleanliness. The results of the research show that the activities of the Curtain Program, the Night Waste Disposal Program (persami), the Denai Fast Waste Service (persad), and the Waste Movement Program for stunting Denai (Denai caregivers) have improved environmental cleanliness and health in the Medan Denai District area. Apart from that, the district government and the community are committed to carrying out the program in a sustainable manner.